The Digital Budayawan: Transforming World Music Education Through Online Media - Hayward, Sean (Jurusan Sejarah, Seni, dan Arkeologi, FKIP, Universitas Jambi, 2024)
In recent years, the integration of internet technology, particularly platforms like YouTube, has revolutionized the way that we learn about arts and culture. This presentation explores the concept of the